Intravitreal implantation of TPP1-transduced stem cells delays retinal degeneration in canine CLN2 neuronal ceroid lipofuscinosis. (November 2016) - Tracy, Christopher J.; Whiting, Rebecca E.H.; Pearce, Jacqueline W.; Williamson, Baye G.; Vansteenkiste, Daniella P.; Gillespie, Lauren E.; Castaner, Leilani J.; Bryan, Jeffrey N.; Coates, Joan R.; Jensen, Cheryl A.; Katz, Martin L.
Abstract: The CLN2 form of neuronal ceroid lipofuscinosis is a neurodegenerative disease that results from mutations in the TPP1 gene. Affected children exhibit progressive declines in most neurological functions including vision. Functional declines are accompanied by progressive brain and retinal atrophy. TPP1 encodes the soluble lysosomal enzyme tripeptidyl peptidase-1 (TPP1). Dachshunds with a TPP1 null mutation exhibit a disorder very similar to human CLN2 disease. Periodic infusion of recombinant TPP1 protein or a single injection of a TPP1 gene therapy vector into the cerebrospinal fluid of affected dogs significantly delays the onset and progression of neurological signs but does not slow vision loss or retinal degeneration. Studies were conducted to determine whether intravitreal implantation of autologous bone marrow derived stem cells transduced with a TPP1 expression construct would inhibit retinal degeneration in the canine model. A single injection of the transduced cells at an early stage in the disease progression substantially inhibited the development of disease-related retinal function deficits and structural changes. No adverse effects of the treatment were detected. These findings indicate that ex vivo gene therapy using autologous stem cells is an effective means of achieving sustained delivery of therapeutic compounds to tissues such as the retina for which systemic administration would be ineffective. Highlights: Progressive retina degeneration occurs CLN2 neuronal ceroid lipofuscinosis. Retina degeneration results from absence of lysosomal enzyme TPP1. Ex vivo gene therapy preserves retinal structure and function in CLN2 disease.